What keeps them invested? Social identity and group formation in blockchain - Aebli, Annika; Silberstein-Bamford, Fabienne; Bamford, Joshua S. (Frontiers in Blockchain, 2025)
Cryptocurrency technologies have spawned a vast network of millions of users. One notable aspect of crypto spaces is the emergence of vibrant communities that form around specific projects, with supporters gathering on interactive online platforms and demonstrating a strong sense of collective identity. Despite its pseudonymous and “trustless” nature, crypto has become an instrument for establishing social ties that seem remarkably robust. However, the factors that influence establishing social bonds in highly dispersed, pseudonymous crypto spaces with minimal in-person interaction have remained largely unexplored so far. Using a mixed-method approach, this study examines the factors that shape community formation in the crypto space. In an initial step, based on 26 semi-structured, qualitative interviews, we explore factors that may influence group formation in crypto spaces. In a second step, we develop a quantitative questionnaire using items generated from these interviews to measure the effect of the identified factors on group formation, using a sample of 111 crypto users. Group formation is operationalised as an identity fusion scale, reflecting the tendency for individuals to merge their sense of self with that of a social group to which they belong. The results show that social reward, a promising outlook, and participant’s investment level predict identity fusion with crypto communities. This study contributes to the understanding of social bonding processes in pseudonymous crypto spaces.